2017
DOI: 10.1080/02640414.2017.1356025
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a home-based physical activity intervention on cardiorespiratory fitness in breast cancer survivors; a randomised controlled trial

Abstract: The aim of this current randomised controlled trial was to evaluate the effects of a home-based physical activity (PA) intervention on cardiorespiratory fitness in breast cancer survivors. Thirty-two post-adjuvant therapy breast cancer survivors (age = 52 ± 10 years; BMI = 27.2 ± 4.4 kg∙m) were randomised to a six-month home-based PA intervention with face-to-face and telephone PA counselling or usual care. Cardiorespiratory fitness and self-reported PA were assessed at baseline and at six-months. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Lahart et al . [29] conducted a six-month randomized controlled trial of a home-based physical activity intervention involving 32 breast cancer survivors. Magnitude-based inference analyses revealed at least small beneficial effects on absolute and relative VȮ 2 max (cardiorespiratory fitness), and total and moderate physical activity in the intervention compared to the usual care group.…”
Section: Resultsmentioning
confidence: 99%
“…Lahart et al . [29] conducted a six-month randomized controlled trial of a home-based physical activity intervention involving 32 breast cancer survivors. Magnitude-based inference analyses revealed at least small beneficial effects on absolute and relative VȮ 2 max (cardiorespiratory fitness), and total and moderate physical activity in the intervention compared to the usual care group.…”
Section: Resultsmentioning
confidence: 99%
“…Only 15% of studies reported any a priori power analysis. In cases where authors reported sample size calculations based on the MBI calculators, they often reported very low sample size requirements, such as 5, 6, or 7 total participants [22][23][24]. We also note that many authors seemed to erroneously believe that use of MBI circumvents the need for an adequate sample size [25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…N per group for studies with >1 group (n = 111) a 10 [8,15] Total N for single group studies (n = 121) 14 [10,24] Number of dependent variables 7 [5,12] Number Some authors explicitly set a minimum evidence threshold above which effects were declared "implementable", "substantial", or "practically meaningful." Others implicitly set this threshold by only choosing to highlight and draw conclusions based on effects that met a given evidentiary threshold, such as "likely" or "possible.…”
Section: Measure Median [Iqr] or N(%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Only 15% of studies reported any a priori power analysis. In cases where authors reported sample size calculations based on the MBI calculators, they often reported very low sample size requirements, such as 5, 6, or 7 total participants [22][23][24]. We also note that many authors seemed to erroneously believe that use of MBI circumvents the need for an adequate sample size [25][26][27][28][29] In these cases, authors wrote a version of the following statements: "When the positive and negative values were both >5%, the inference was classified as unclear" or, equivalently, "If the 90% confidence interval overlapped the thresholds for the smallest worthwhile positive and negative effects, effects were classified as unclear"; this means they used 1ℎ =5% and treated both directions equivalently, consistent with non-clinical MBI.…”
Section: Resultsmentioning
confidence: 99%